Religious Violence in Education in the 1970s and 1990s in the Peruvian Andean Southern Centre - Taipe, Néstor (Revista Electrónica Educare, 2023)
Objectives. This article aims to determine the causes of religious violence by teaching staff towards students in the context of the Peruvian Andean region during the 1970s and 1990s, describe the forms adopted by this violence, and explain its effects on the students. Methodology. This is an analytical-synthetic and interpretive-explanatory study based on ethnographic research with primary and secondary sources. Results. Mechanisms of religious violence were recorded with oral and visual codes. The analysis of these mechanisms led to the proposition that the school imposes rules that ideally regulate the relationships between teachers and students. Conclusions. Ideal patterns conflict with the emergence of transgressions of the imposed rules. Therefore, the institution applies religious violence as coercion and social control to induce fear in transgressors to pay for their sins through mystical punishments. From this perspective, fear acts as a cultural device of domination that brings, as an immediate effect, the submission of male and female students to authority and, as a mediate effect, rejection of the Catholic Church.